Beyond Belief: How the "Corroboration Rule" in Malawi Obstructs Justice for Victims of Sex Crimes and Discriminates Against Women and Girls on the Basis of Sex—A Call for Legislative Change - Liu, Michelle Xiao; Creel Benton, Alexandra K. (Columbia Journal of Gender and Law, 2021)
Sexual abuse against women and girls in Malawi is pervasive, and survivors face significant barriers in their quest for justice. One particular barrier—the “corroboration rule”—stands out as a discriminatory and onerous roadblock for women and girls who seek justice as victims of sex crimes. The corroboration rule is a common law rule of evidence and criminal procedure that requires prosecutors trying sex offence cases to have independent evidence in addition to a victim’s testimony, even if that testimony is credible and shows beyond a reasonable doubt that the defendant committed the sex crime. This heightened evidentiary standard for victims of sex crimes is based on the stereotype that women and girls are apt to lie about being raped and that their word alone—no matter how clear, convincing, or credible—should not be enough to put a rapist behind bars. Because of the rule, too many women and girls in Malawi are not treated equally in the criminal justice system, and rarely are those who sexually abuse them brought to justice in court. This fosters a climate of impunity for rapists and sexual abusers. While many countries around the world used to require the corroboration rule in sexual offences, in the modern era, Malawi stands apart from the rest of the world as one of the few countries that still requires its use as a matter of common law. However, with a constitution that guarantees equality for women and girls and equal access to justice under the law, and as a State Party to treaties that guarantee the same, Malawi’s Parliament should abolish the corroboration rule.